A composite MOF membrane for gas separation and preparation method thereof
By loading the composite of glass MOF and MIL-101 (Cr) on the α-Al2O3 substrate and filling the defects by melting the MOF through heat treatment, the defect problems existing in the MOF film in gas separation are solved, and efficient gas separation performance is achieved.
Patent Information
- Application Number
- CN202411911465.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The defects and problems of MOF membranes in gas separation lead to low gas separation efficiency, limiting their application prospects.
Using a composite MOF membrane, a composite of MOF-A (glass MOF) and MOF-B (such as MIL-101 (Cr)) is loaded on an α-Al2O3 substrate and MOF-A is melted into liquid state by heat treatment to fill the defects between MOF-B particles.
A defect-free, continuous and dense MOF gas separation membrane is achieved, which improves the gas separation performance, especially in H2/CO2 separation, which shows a high gas permeability.
Smart Images

Figure CN119345918B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas separation membranes, and in particular relates to a composite MOF membrane for gas separation and a preparation method thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are porous materials with periodic framework structures that are connected to organic ligands through coordination bonds using metal ions or metal clusters as nodes. They have the characteristics of adjustable porosity, high specific surface area, and easy functionalization. Based on these characteristics, MOFs have broad application prospects in many fields, especially in the field of gas separation membranes. Currently, a wide variety of MOF materials have been reported. However, the inevitable defects of MOF membranes reduce the separation efficiency of MOF membranes and limit the further development of MOF membranes.
[0003] To solve this problem, many researchers have been committed to exploring ways to reduce MOF membrane defects and have developed various post-treatment methods. Although the gas separation selectivity of the treated MOF membranes has been improved, the gas flux has decreased and the defect problem still exists.
[0004] As an emerging MOF material, MOF glass is usually prepared by melt quenching, that is, heat treatment of MOF crystals to melt them, and then rapid cooling to solidify the MOF liquid to form glass. MOF glass has the following characteristics: 1) The formation process of MOF glass includes solid-liquid phase transition, and the formation of liquid makes it easier to process; 2) During the melting process, MOF glass loses its long-range disordered structure, retains the short-range ordered units, and eliminates grain boundaries; 3) There are micropores or ultramicropores and permanent porosity.
[0005] During the melting process, MOF glass materials retain their ultramicroporous structure, but their long-range disorder and discontinuous pores result in low gas permeation flux of MOF glass membranes, limiting their application in gas separation.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a composite MOF membrane for gas separation and a preparation method thereof to solve the above problems.
[0008] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0009] The present invention firstly provides a composite MOF membrane for gas separation, wherein the composite MOF membrane comprises a substrate and a MOF material supported on the substrate;
[0010] The substrate includes any one of polypropylene (PP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and α-Al2O3;
[0011] Preferably, the substrate is α-Al2O3;
[0012] The MOF material is a composite of MOF-A and MOF-B;
[0013] The MOF-B includes one or more of ZIF-9, ZIF-67, UiO-66, ZIF-8, and MIL-101(Cr); preferably, the MOF-B is MIL-101(Cr);
[0014] The MOF-A is a glass MOF. The glass MOF is a MOF that has the ability to transform from a crystalline state to an amorphous glass state;
[0015] Preferably, the glass MOF includes any one or more of ZIF-62, ZIF-76, ZIF-4, TIF-4, and Zn-P-dmbIm; further preferably, the glass MOF is Zn-P-dmbIm.
[0016] The present invention also provides a method for preparing the composite MOF membrane for gas separation, the method comprising the following steps:
[0017] S1: Preparation of MOF-B suspension;
[0018] S2: Preparation of MOF-A suspension;
[0019] The ratio of the mass of MOF-B in the MOF-B suspension to the mass of MOF-A in the MOF-A suspension is 1:10-20, preferably 1:15; due to defects on the surface of the membrane, a certain amount of MOF-A is required to fill and repair in order to obtain a continuous and dense composite membrane;
[0020] S3: The MOF-B suspension obtained in S1 is filtered onto the substrate to obtain MOF membrane 1, and then the MOF-A suspension obtained in S2 is filtered onto the MOF membrane 1 to obtain MOF membrane 2 after drying, and MOF membrane 2 is heat-treated to melt it, and the composite MOF membrane is obtained after cooling.
[0021] Preferably, when the MOF-B is MIL-101(Cr) and the MOF-A is Zn-P-dmbIm, the method comprises the following steps:
[0022] S1: dissolving chromium nitrate nonahydrate and terephthalic acid in deionized water, mixing evenly, adding an appropriate amount of hydrofluoric acid, and then pouring the obtained mixed solution into a stainless steel high-pressure reactor lined with a polytetrafluoroethylene container to react at high temperature, cooling to room temperature after the reaction, centrifuging and washing in sequence, and placing the obtained product in a certain amount of ethanol solution to obtain a MIL-101 (Cr) suspension;
[0023] S2: zinc acetate dihydrate, 5,6-dimethylbenzimidazole and phosphoric acid are mixed and ground to obtain a powder, which is washed three times with dichloromethane and then placed in a certain amount of dichloromethane solution to obtain a Zn-P-dmbIm suspension;
[0024] S3: Take a suspension containing a certain amount of MIL-101 (Cr), add a certain amount of ethanol solution, and disperse it evenly by ultrasonication; take a suspension containing a certain amount of Zn-P-dmbIm, add a certain amount of dichloromethane solution, and disperse it evenly by ultrasonication; wherein the mass ratio of MIL-101 (Cr) to Zn-P-dmbIm is 1:10-20, preferably 1:15; firstly, the evenly dispersed MIL-101 (Cr) suspension is filtered and placed on an α-Al2O3 substrate to obtain MOF membrane one, and then the evenly dispersed Zn-P-dmbIm suspension is continuously filtered to the MOF membrane one, and dried in an oven at 60-80°C to obtain MOF membrane two, and then the obtained MOF membrane two is heat-treated in a nitrogen atmosphere to melt it, and the composite MOF membrane is obtained after cooling.
[0025] Preferably, the heat treatment temperature is 200-210°C and the time is 0.5-1h;
[0026] Further preferably, the heat treatment includes placing the MOF membrane 2 on an aluminum foil.
[0027] More preferably, the heat treatment further comprises: placing the side of the MOF membrane loaded with the MOF material on an aluminum foil sheet, and then heating it to melt it.
[0028] MOF glass can be obtained by heating the crystal to melt into a liquid state and then quenching it, but most MOF crystals will undergo skeleton collapse and irreversible thermal decomposition when heated, and will not be converted into a molten state. At present, only a small amount of MOF materials can be converted into a glassy state, such as ZIF-62, ZIF-76, ZIF-4, TIF-4, etc. The melting points of the above MOF materials are relatively high, which are 430°C, 477°C, 593°C, and 467°C, respectively, while the melting point of Zn-P-dmbIm is relatively low, and it can be converted into a glassy state at 200~210°C, which can significantly reduce the energy consumption during the experiment. In addition, Zn-P-dmbIm has a low viscosity when melted into a liquid state, showing good fluidity and processability. Therefore, Zn-P-dmbIm is preferably used as the MOF glass of the present invention.
[0029] MIL-101(Cr) is assembled from metallic chromium and organic ligand terephthalic acid, and has two different sizes of mesoporous cage cavities, with diameters of 29Å and 34Å, respectively, and a pore window diameter of up to 16Å, with the characteristics of large specific surface area and pore volume, high thermal stability, etc. As MOF-B of the present invention, compared with MOF materials such as ZIF-9, ZIF-67, UiO-66, and ZIF-8, MIL-101(Cr) has a larger pore window diameter and specific surface area, which is beneficial to the separation of gas molecules.
[0030] The structures of currently commonly used polymer substrates such as polypropylene (PP), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and other materials may change after long-term heating. The present invention preferably uses the high-temperature resistant inorganic ceramic membrane material α-Al2O3 as the substrate. Since the surface of the α-Al2O3 substrate contains a large number of pore structures, in order to promote the diffusion of the glass MOF melt, the placement of the membrane is adjusted. Unlike the conventional method of placing the α-Al2O3 substrate side of the membrane on an aluminum foil for heating, the present invention innovatively inverts the membrane, places its active side, i.e., the side loaded with MOF material, on an aluminum foil and then heats it. Through capillary action, the surface of the α-Al2O3 substrate is easily filled with the MOF melt.
[0031] The present invention utilizes the liquid phase state of MOF glass material during melting to repair the defects of conventional MOF membranes, thereby obtaining a defect-free, continuous and dense MOF gas separation membrane, thereby improving gas separation performance.
[0032] In particular, the fusible and low-melting-point Zn-P-dmbIm glass MOF is used as a repair agent to repair the MOF particles deposited on the α-Al2O3 substrate, thereby obtaining a continuous and dense gas separation membrane.
[0033] Beneficial effects of the present invention:
[0034] The MOF composite film provided by the present invention comprises a substrate and a composite MOF. The glass MOF in the composite MOF can be melted into a liquid state after heat treatment, and then rapidly cooled to solidify the MOF liquid to form glass. During the melting process, the MOF glass loses the long-range disordered structure, retains the short-range ordered units, and eliminates the grain boundaries. As a repairing agent, the defects in the conventional MOF film are repaired, thereby obtaining a defect-free, continuous and dense composite film.
[0035] The method of the invention has universal applicability, simple operation steps, strong repeatability and controllable generation conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A scanning electron microscope image of the MIL-101(Cr) particles provided in Example 1;
[0038] Figure 2 A scanning electron microscope image of the Zn-P-dmbIm particles provided in Example 1;
[0039] Figure 3 A surface scanning electron microscope image of the MIL-101(Cr) / α-Al2O3 film provided in Example 2;
[0040] Figure 4 MIL-101(Cr)@a provided in Example 2 g Surface scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film;
[0041] Figure 5 A provided for Comparative Example 1 g Surface scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film;
[0042] Figure 6 A cross-sectional scanning electron microscope image of the MIL-101(Cr) / α-Al2O3 film provided in Example 2;
[0043] Figure 7 MIL-101(Cr)@a provided in Example 2 g Cross-sectional scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film;
[0044] Figure 8 A provided for Comparative Example 1 g Cross-sectional scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film;
[0045] Fig. 9 MIL-101(Cr)@a provided in Example 1 g Surface scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film-1;
[0046] Fig.10 MIL-101(Cr)@a provided in Example 1 g Cross-sectional scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film-1;
[0047] Fig.11 MIL-101(Cr) / α-Al2O3, MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3, MIL-101(Cr)@a g X-ray diffraction pattern of Zn-P-dmbIm / α-Al2O3 film;
[0048] Fig.12 This is a comparison chart of H2 / CO2 separation performance of gas separation membranes. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0050] Example 1
[0051] This embodiment provides a composite MOF membrane for gas separation, and the preparation method thereof is as follows:
[0052] S1: Preparation of MIL-101(Cr) suspension:
[0053] Chromium nitrate nonahydrate (4 g, 1 mmol) and terephthalic acid (1.66 g, 1 mmol) were dissolved in 48 mL of deionized water, mixed evenly, and 0.4 mL of hydrofluoric acid was added; the mixed solution was poured into a stainless steel autoclave lined with a polytetrafluoroethylene container, reacted in an oven at 220°C for 8 hours, and naturally cooled to room temperature after the reaction was completed. The obtained product was centrifuged and washed three times with hot DMF and hot ethanol respectively to obtain MIL-101 (Cr) particles. Finally, the obtained MIL-101 (Cr) particles were placed in a certain amount of ethanol solution to obtain a MIL-101 (Cr) suspension;
[0054] The scanning electron microscope image of the MIL-101(Cr) particles prepared in this step is as follows: Figure 1 As shown by Figure 1 It can be seen that the MIL-101(Cr) particles synthesized in this embodiment have a symmetrical octahedral structure and a size of about 1µm to 1.5µm.
[0055] S2: Preparation of Zn-P-dmbIm suspension:
[0056] Zinc acetate dihydrate (219.5 mg, 1 mmol), 5,6-dimethylbenzimidazole (292.4 mg, 2 mmol) and phosphoric acid (210 μL, 3 mmol) were placed in a mortar and manually ground for 15 minutes. The obtained powder sample was washed three times with dichloromethane to obtain Zn-P-dmbIm particles. Finally, the obtained Zn-P-dmbIm particles were placed in a certain amount of dichloromethane solution to obtain a Zn-P-dmbIm suspension.
[0057] The scanning electron microscope image of the Zn-P-dmbIm particles prepared in this step is as follows: Figure 2 As shown by Figure 2 It can be seen that the particle size of Zn-P-dmbIm prepared in this step is 300nm~1µm.
[0058] S3: Preparation of MIL-101(Cr)@a g Zn-P-dmbIm / α-Al2O3 film:
[0059] Take a suspension containing 0.05 mg MIL-101 (Cr), add a certain amount of ethanol solution, and use an ultrasonic cell crusher to ultrasonicate to obtain a more uniformly dispersed suspension; take a suspension containing 0.75 mg Zn-P-dmbIm, add a certain amount of dichloromethane solution, and ultrasonicate to make it uniformly dispersed; use a circulating water vacuum pump to vacuum filter, and the filtration pressure is -0.08 MPa: First, the MIL-101 (Cr) suspension is filtered and placed on an α-Al2O3 substrate to obtain MIL-101 (Cr) / α- Al2O3, and then continue to filter the Zn-P-dmbIm suspension, and dry it in an oven at 70°C overnight to evaporate the residual solvent to obtain MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 membrane. The α-Al2O3 substrate side is directly placed on an aluminum foil sheet, kept at 205°C for 1 hour under a nitrogen atmosphere, and naturally cooled to room temperature. The obtained composite membrane is recorded as MIL-101(Cr)@a g Zn-P-dmbIm / α-Al2O3 film-1.
[0060] Example 2
[0061] This embodiment provides a composite MOF membrane for gas separation, and the preparation method thereof is as follows:
[0062] S1: Preparation of MIL-101(Cr) suspension:
[0063] Chromium nitrate nonahydrate (4 g, 1 mmol) and terephthalic acid (1.66 g, 1 mmol) were dissolved in 48 mL of deionized water, mixed evenly, and 0.4 mL of hydrofluoric acid was added; the mixed solution was poured into a stainless steel autoclave lined with a polytetrafluoroethylene container, reacted in an oven at 220°C for 8 hours, and naturally cooled to room temperature after the reaction was completed. The obtained product was centrifuged, washed three times with hot DMF and hot ethanol respectively to obtain MIL-101 (Cr) particles, and finally placed in a certain amount of ethanol solution to obtain a MIL-101 (Cr) suspension;
[0064] S2: Preparation of Zn-P-dmbIm suspension:
[0065] Zinc acetate dihydrate (219.5 mg, 1 mmol), 5,6-dimethylbenzimidazole (292.4 mg, 2 mmol) and phosphoric acid (210 μL, 3 mmol) were placed in a mortar and manually ground for 15 minutes. The obtained powder sample was washed three times with dichloromethane to obtain Zn-P-dmbIm particles, which were finally placed in a certain amount of dichloromethane solution to obtain a Zn-P-dmbIm suspension;
[0066] S3: Preparation of MIL-101(Cr)@a gZn-P-dmbIm / α-Al2O3 film:
[0067] Take a suspension containing 0.05 mg MIL-101 (Cr), add a certain amount of ethanol solution, and use an ultrasonic cell crusher to obtain a more uniformly dispersed suspension; take a suspension containing 0.75 mg Zn-P-dmbIm, add a certain amount of dichloromethane solution, and use ultrasonic to make it uniformly dispersed; use a circulating water vacuum pump to vacuum filter, and the filtration pressure is -0.08 MPa; first, filter the MIL-101 (Cr) suspension onto an α-Al2O3 substrate to obtain MIL- 101(Cr) / α-Al2O3 membrane, and then continue to filter the Zn-P-dmbIm suspension, and dry it in an oven at 70°C overnight to evaporate the residual solvent to obtain MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 membrane. The side loaded with MOF material is directly in contact with aluminum foil, and the α-Al2O3 substrate side is not in direct contact with the aluminum foil. It is kept at 205°C for 1 hour under a nitrogen atmosphere and naturally cooled to room temperature. The obtained composite membrane is recorded as MIL-101(Cr)@a g Zn-P-dmbIm / α-Al2O3 film.
[0068] Figure 3 The surface scanning electron microscope image of the MIL-101(Cr) / α-Al2O3 film provided in this embodiment is as follows: Figure 4 MIL-101(Cr)@a provided in this embodiment g Surface scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film.
[0069] Example 3
[0070] S1: Preparation of ZIF-8 suspension:
[0071] Zinc nitrate hexahydrate (734.4 mg, 2.469 mmol) was dissolved in 50 mL of methanol and recorded as solution 1. 2-Methylimidazole (810.6 mg, 9.874 mmol) and 1-methylimidazole (810.6 mg, 9.874 mmol) were dissolved in 50 mL of methanol and recorded as solution 2. Under stirring, solution 2 was poured into solution 1, and stirring was stopped after the two solutions were completely mixed. After reacting at ambient temperature for 24 hours, the resulting product was centrifuged and washed three times with methanol to obtain ZIF-8 particles, which were finally placed in a certain amount of methanol solution to obtain a ZIF-8 suspension.
[0072] S2: Preparation of ZIF-8(Cr)@a g Zn-P-dmbIm / α-Al2O3 film:
[0073] Take a suspension containing 0.05 mg ZIF-8, add a certain amount of methanol solution, and use an ultrasonic cell crusher to ultrasonicate to obtain a more uniformly dispersed suspension; take a suspension containing 0.75 mg Zn-P-dmbIm, add a certain amount of dichloromethane solution, and ultrasonicate to make it uniformly dispersed; use a circulating water vacuum pump for vacuum filtration, and the filtration pressure is -0.08 MPa: first, the ZIF-8 suspension is filtered and placed on an α-Al2O3 substrate to obtain a ZIF-8 / α-Al2O3 membrane, and then the Zn-P-dmbIm suspension is filtered and dried in an oven at 70°C overnight to evaporate the residual solvent to obtain a ZIF-8@Zn-P-dmbIm / α-Al2O3 membrane, and the side loaded with the MOF material is directly in contact with the aluminum foil, and the α-Al2O3 substrate side is not directly in contact with the aluminum foil, and it is kept at 205°C for 1 hour under a nitrogen atmosphere, and naturally cooled to room temperature to obtain ZIF-8@a g Zn-P-dmbIm / α-Al2O3 film.
[0074] Comparative Example 1
[0075] This comparative example provides a composite MOF membrane, and its preparation method is as follows:
[0076] Take a suspension containing 0.75 mg Zn-P-dmbIm, add a certain amount of dichloromethane solution, and disperse it evenly by ultrasound. Use a circulating water vacuum pump for vacuum filtration, and the filtration pressure is -0.08 MPa. Filter the Zn-P-dmbIm suspension onto an α-Al2O3 substrate to obtain Zn-P-dmbIm / α-Al2O3. The side loaded with Zn-P-dmbIm is directly in contact with an aluminum foil, kept at 205°C for 1 hour under a nitrogen atmosphere, and naturally cooled to room temperature to obtain a g Zn-P-dmbIm / α-Al2O3 film.
[0077] a g Surface scanning electron microscopy images of Zn-P-dmbIm / α-Al2O3 films are shown in Figure 5 shown.
[0078] By comparison Figure 3 , Figure 4 and Figure 5 It can be seen that the MIL-101(Cr) particles are deposited on the α-Al2O3 substrate, and there are gaps and obvious defects between the particles. After the MIL-101(Cr) particles and Zn-P-dmbIm particles are heat treated, the obtained MIL-101(Cr)@a gThe surface of the Zn-P-dmbIm / α-Al2O3 film is flat and uniform without obvious defects, indicating that the Zn-P-dmbIm particles have completely transformed from the crystalline state to the glassy state and filled the gaps between the MIL-101(Cr) particles. The morphology of the Zn-P-dmbIm particles in Comparative Example 1 changed significantly after melting treatment. g The surface of the Zn-P-dmbIm / α-Al2O3 film is uniform and crack-free, and no Zn-P-dmbIm particles are observed, indicating that the Zn-P-dmbIm particles are completely transformed from the crystalline state to the amorphous state.
[0079] Figure 6 This is a cross-sectional scanning electron microscope image of the MIL-101(Cr) / α-Al2O3 film provided in Example 2. Figure 7 MIL-101(Cr)@a provided in Example 2 g Cross-sectional scanning electron micrograph of Zn-P-dmbIm / α-Al2O3 film. Figure 8 A provided for Comparative Example 1 g Cross-sectional scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film; Figure 6-8 The results show that the MIL-101(Cr) particles are stacked and distributed on the α-Al2O3 substrate, and the particle thickness is about 2µm. After heat treatment of the MIL-101(Cr) particles and Zn-P-dmbIm particles, MIL-101(Cr)@a g The cross section of the Zn-P-dmbIm / α-Al2O3 film is relatively flat and uniform, with a thickness of about 2.8µm. When the Zn-P-dmbIm particles become liquid during the melting process, they will penetrate into the gaps between the MIL-101(Cr) particles to fill their gaps, thereby repairing them. After the Zn-P-dmbIm particles are deposited on the α-Al2O3 substrate and heat treated, a g The Zn-P-dmbIm / α-Al2O3 film has a flat, uniform cross section without defects and a thickness of about 1.5µm. g From the scanning electron microscopy image of the cross section of the Zn-P-dmbIm / α-Al2O3 membrane, it can be seen that the glassy state has penetrated into the pores on the surface of the α-Al2O3 substrate in large quantities, and the surface layer of the substrate is filled with the MOF melt.
[0080] Fig. 9 MIL-101(Cr)@a provided in Example 1 g Surface scanning electron microscopy image of Zn-P-dmbIm / α-Al2O3 film-1; Fig.10 MIL-101(Cr)@a provided in Example 1 g Cross-sectional scanning electron micrograph of Zn-P-dmbIm / α-Al2O3 film-1; Fig. 9 and Fig.10 It can be seen that the obtained MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 film, whose α-Al2O3 substrate side is directly placed on the aluminum foil, is heat-treated to obtain the composite film MIL-101(Cr)@a g The surface of Zn-P-dmbIm / α-Al2O3 film-1 is uneven, and there are still gaps and obvious defects. When Zn-P-dmbIm is melted into liquid, it fails to diffuse evenly and does not completely penetrate into the gaps between MIL-101(Cr) particles to fill their gaps, thus failing to play a good repair role.
[0081] Fig.11 MIL-101(Cr) / α-Al2O3, MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3, MIL-101(Cr)@a g X-ray diffraction pattern of Zn-P-dmbIm / α-Al2O3 film; Fig.11 It can be seen that MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3, MIL-101(Cr)@a g The X-ray diffraction pattern of Zn-P-dmbIm / α-Al2O3 does not show obvious characteristic peaks of MIL-101(Cr), which may be due to the small content of MIL-101(Cr) particles in the film (0.05 mg). Zn-P-dmbIm particles show high crystallinity and match well with the simulated X-ray diffraction pattern of Zn-P-dmbIm. MIL-101(Cr)@a g The X-ray diffraction pattern of Zn-P-dmbIm / α-Al2O3 only shows the characteristic peaks of the α-Al2O3 substrate, while the characteristic peaks of Zn-P-dmbIm disappear, indicating that Zn-P-dmbIm is transformed from a crystalline state to an amorphous glassy state.
[0082] Fig.12 MIL-101(Cr)@a provided for this application g Comparison of H2 / CO2 separation performance of Zn-P-dmbIm / α-Al2O3 membrane and other conventional membranes; Fig.12 It can be seen that most conventional H2 / CO2 separation membranes have low H2 permeability and good selectivity. g The Zn-P-dmbIm / α-Al2O3 membrane exhibits high gas permeability, which is superior to the separation performance of most H2 / CO2 separation membranes.
[0083] The performance test results of the membranes provided in Examples 2, 3 and Comparative Example 1 are shown in Table 1 below:
[0084] Table 1 Performance test results of the membranes provided in Examples 2, 3 and Comparative Example 1
[0085]
[0086] First, we can see from Table 1 that a g The permeability of H2 and CO2 of Zn-P-dmbIm / α-Al2O3 membrane is relatively low, which is mainly attributed to the fact that Zn-P-dmbIm crystals melt into an amorphous glass state after heat treatment. This phase change causes the original skeleton of Zn-P-dmbIm crystals to deform. After vitrification, the overall volume shrinks, the free volume in the pores becomes smaller, the pore continuity is poor, the porosity decreases, and the gas permeability decreases. There are a large number of defects on the surface of MIL-101(Cr) / α-Al2O3 membrane, so it exhibits higher permeability of H2 and CO2 and lower gas selectivity. The fusible Zn-P-dmbIm glass MOF acts as a repair agent. When it becomes liquid during the melting process, it will penetrate into the gaps between MIL-101(Cr) particles to fill their gaps and repair them, thereby obtaining a continuous and dense MIL-101(Cr)@a g In addition, due to the microporous structure and high specific surface area of MIL-101(Cr), the 101(Cr)@a g Increase in gas permeability of Zn-P-dmbIm / α-Al2O3 membrane.
[0087] As shown in Table 1, in Example 1, the surface of the MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 membrane loaded with MOF material was facing upward, and the α-Al2O3 substrate was placed on an aluminum foil sheet, and melted by heat treatment to obtain MIL-101(Cr)@a g The permeability and selectivity of H2 and CO2 of Zn-P-dmbIm / α-Al2O3-1 membrane are lower than those of Example 2. The membrane is inverted, and the side loaded with MOF material is directly in contact with the aluminum foil. The α-Al2O3 substrate is not directly in contact with the aluminum foil. The MIL-101(Cr)@a obtained by heating g This is because when the MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 film is heated in the normal positive direction in Example 1, the Zn-P-dmbIm is diffused unevenly when it is melted into a liquid state, and it fails to penetrate into the surface pores of the α-Al2O3 substrate through extrusion, resulting in that the defects on the surface of the MIL-101(Cr) / α-Al2O3 film are not completely filled and repaired, so the obtained MIL-101(Cr)@a gThere are still defects on the surface of the Zn-P-dmbIm / α-Al2O3-1 film. Example 2 successfully solved this problem by adjusting the placement of the MIL-101(Cr)@Zn-P-dmbIm / α-Al2O3 film, achieving complete repair of the film surface defects.
[0088] As shown in Table 1, ZIF-8 is formed by the coordination of divalent zinc ions and 2-methylimidazole, has excellent chemical stability and thermal stability, and is the most commonly studied ZIF series MOF. Therefore, this application also uses ZIF-8 as the MOF material to prepare ZIF-8 / α-Al2O3 and ZIF-8@a g The H2 / CO2 separation performance of Zn-P-dmbIm / α-Al2O3 membrane was tested. g The permeability of H2 and CO2 of Zn-P-dmbIm / α-Al2O3 membrane is lower than that of MIL-101(Cr)@a g Zn-P-dmbIm / α-Al2O3 membrane, which is due to the fact that the pore diameter (about 3.4Å) and specific surface area of ZIF-8 are smaller than those of MIL-101(Cr).
[0089] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a composite MOF membrane for gas separation, characterized in that: The method comprises the following steps: S1: preparing a MOF-B suspension, wherein the MOF-B is MIL-101(Cr); S2: preparing a MOF-A suspension, wherein the MOF-A is a glass MOF capable of transforming from a crystalline state to an amorphous glass state; the glass MOF is Zn-P-dmbIm; S3: The MOF-B suspension obtained in S1 is filtered to the substrate α-Al2O3 to obtain MOF membrane 1, and then the MOF-A suspension obtained in S2 is filtered to the MOF membrane 1, and the MOF membrane 2 is obtained after drying, and the MOF membrane 2 is heat-treated to melt it, and the composite MOF membrane is obtained after cooling; The heat treatment comprises: placing the side of the MOF membrane loaded with the MOF material on an aluminum foil, and then heating it to 200-210° C. and maintaining it for 0.5-1 h to melt it.
2. The preparation method according to claim 1, characterized in that: The ratio of the mass of MOF-B in the MOF-B suspension to the mass of MOF-A in the MOF-A suspension is 1:10-20.
3. The preparation method according to claim 1, characterized in that: The method further comprises the steps of: S1: dissolving chromium nitrate nonahydrate and terephthalic acid in deionized water, mixing evenly, adding an appropriate amount of hydrofluoric acid, and then pouring the obtained mixed solution into a stainless steel high-pressure reactor lined with a polytetrafluoroethylene container to react at high temperature, cooling to room temperature after the reaction, centrifuging and washing in sequence, and placing the obtained product in a certain amount of ethanol solution to obtain a MIL-101 (Cr) suspension; S2: zinc acetate dihydrate, 5,6-dimethylbenzimidazole and phosphoric acid are mixed and ground to obtain a powder, which is washed three times with dichloromethane and then placed in a certain amount of dichloromethane solution to obtain a Zn-P-dmbIm suspension; S3: Take a certain amount of MIL-101(Cr) suspension, add ethanol solution, and disperse it evenly by ultrasonication; take a certain amount of Zn-P-dmbIm suspension, add dichloromethane solution, and disperse it evenly by ultrasonication; The mass ratio of MIL-101 (Cr) to Zn-P-dmbIm is 1:10-20; first, the uniformly dispersed MIL-101 (Cr) suspension is filtered and placed on an α-Al2O3 substrate to obtain a MOF membrane one, and then the uniformly dispersed Zn-P-dmbIm suspension is continuously filtered to the MOF membrane one, and the MOF membrane two is dried in an oven at 60-80°C to obtain a MOF membrane two, and then the obtained MOF membrane two is heat-treated in a nitrogen atmosphere to melt it, and the composite MOF membrane is obtained after cooling.
Citation Information
Patent Citations
Ionic liquid composite membrane supported by nano metal organic framework ZIF-8, preparation method and application thereof
CN112191110A
Polyimide mixed matrix membrane as well as preparation method and application thereof
CN118904120A